Psychological Well-being of Individuals Living A Minimalist Lifestyle: A Phenomenological Study - Trisna Wati; Riva Tri Rahmawati; Ilma Rizqa Arshanty; Nesya Adira (Faculty of Psychology, Universitas Negeri Yogyakarta, 2025)
The minimalist lifestyle has gained popularity among the public due to its widespread information across various platforms. Minimalism, a way for individuals to live their lives simply, orderly, and elegantly, is closely related to their psychological well-being. This study aims to explore the reasons, processes, and benefits of psychological well-being associated with a minimalist lifestyle. This research adopts a qualitative approach using a phenomenological method and involves four minimalist individuals (over 24 years old) from different regions of Indonesia. Data collection involved interviews and literature review. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The study results indicate that participants perceived minimalism as a lifestyle focused on simplicity, minimizing various aspects of life, and making the most of it. Participants reported experiencing improved well-being after embracing a minimalist lifestyle, including greater self-acceptance, positive relationship quality, self-autonomy personal growth, environmental mastery, and life goals.